Penanaman Mangrove Sebagai Bentuk Kegiatan Penanggulangan Dan Pelestarian Ekosistem Di Desa Buruk Bakul - Nasrizal Nasrizal; T. M. Habil Agathan; Siti Purani; M. Fikri Abdi; Rizqi Ramadhan; Mia Wahyuni; Vanny Ellysia Putri; Rismawati Rismawati; Ciansi Deby Angraini; Uswatun Sepri Esti; Nora Novita (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Preserving mangroves in coastal areas is the key to maintaining environmental resilience, local economy and sustainability of coastal ecosystems. Plus, Buruk Bakul village, Bengkalis Regency has quite a large coastal area, so it needs conservation and awareness from the community in the mangrove planting movement on the coast so that the mangrove ecosystem is well maintained. Planting activities were carried out involving a combination of students and community organizations to preserve the natural coastal environment. The method used during the service was planting and maintenance using the mollenda and reiser method, namely ADDIE (analysis-design-developing-implement-evaluate) which had a big influence on planting mangroves in Buruk Bakul village.